On the Nature and Evidence of Title to Realty: Maori Law - Maclaurin, Richard C (Victoria University of Wellington Law Review, 1999)
After studying mathematics at Cambridge, Maclaurin turned to the study of law, partly asa result of his friendship with the South African Jan Smuts. As part of his LLM studies hewrote a thesis which was awarded the Yorke essay prize in 1898. The essay was published in1901, making it the first legal book published by a Victoria academic, albeit a Professor of mathematics. Later Maclaurin's position as a Law Professor was formalised but like Salmond he departed, firstly for Columbia and then MIT. Legal Education's loss became Science Education's gain.